To Determine The Maximum Bite Force In Different Skeletal Growth Patterns - Bhardwaj, Madhvi; Gupta, Sweety; Rathaur , Rahul; Kaur Pahwa, Kripleen; Dagdiya, Manish; Gupta, Nishant (Journal of Neonatal Surgery, 2025)
Bite force serves as an indicator of masticatory efficiency and is influenced by multiple factors including age, occlusion, growth pattern, periodontal health, and temporomandibular joint function. This study aimed to assess and compare maximum bite force among individuals with different skeletal growth patterns—vertical, horizontal, and average. A total of 270 subjects aged 18–40 years were selected and categorized according to growth pattern determined through lateral cephalometric analysis. Bite force measurements were obtained in the first molar region using a calibrated strain-gauge transducer, and the mean values were statistically analyzed using ANOVA with significance assessed through p-values. Results indicated that individuals with an horizontal growth pattern exhibited the highest bite force, whereas vertical and average growth patterns demonstrated relatively lower, non-significant differences. The greater bite force observed in horizontal growers is likely attributable to balanced craniofacial morphology and optimal muscle orientation, enhancing masticatory performance. Variations due to measurement technique and individual anatomical differences were also considered. In conclusion, individuals with an horizontal growth pattern demonstrate superior bite force and masticatory efficiency compared to vertical or average growers. Relevant literature on bite force, craniofacial structure, and measurement methodology was reviewed to support the findings.